Problematika Guru Dalam Merancang Media Video Pembelajaran Tematik Di SDN 160 Pekanbaru - Rika Anshari; Febrina Dafit (Jurnal Pendidikan Indonesia, 2022)
Teachers are responsible for developing students' knowledge and developing skill values ​​in students, teachers are also responsible for directing and training their students. In an effort to provide learning and education, teachers must be able to use learning tools in an effort to achieve learning objectives, teachers are also required to be able to develop skills in creating and using learning media that will be used in the learning process. This study aims to find out the problems or obstacles for teachers in designing a learning media type of video media. This study uses a qualitative method, where this research is observed by interacting directly or face to face at the research site. The problems experienced by teachers include the ability to use technological tools in designing learning video media, production equipment used in designing video media and making video improvements if they find errors after reviewing the video media that has been made. teachers have made efforts to overcome the problems experienced, including by studying with teachers who are already proficient in designing video media without having problems and learning independently by looking at the tutorials on the youtube application. From the results of the research above, it can be seen that there are problems that hinder teachers from designing a video media, and teachers at SD Negeri 160 Pekanbaru have the same problems